TAM-targeted reeducation for enhanced cancer immunotherapy: Mechanism and recent progress - Shen, Xinyuan; Zhou, Shengcheng; Yang, Yidong; Hong, Tu; Xiang, Ze; Zhao, Jing; Zhu, Chaojie; Zeng, Linghui; Zhang, Lingxiao (Frontiers in Oncology, 2022)
Tumor-associated macrophages (TAMs) as an important component of tumor microenvironment (TME) are closely related with the occurrence, development, and metastasis of malignant tumors. TAMs are generally identified as two distinct functional populations in TME, i.e., inflammatory/anti-tumorigenic (M1) and regenerative/pro-tumorigenic (M2) phenotype. Evidence suggests that occupation of the TME by M2-TAMs is closely related to the inactivation of anti-tumor immune cells such as T cells in TME. Recently, efforts have been made to reeducate TAMs from M2- to M1- phenotype to enhance cancer immunotherapy, and great progress has been made in realizing efficient modulation of TAMs using nanomedicines. To help readers better understand this emerging field, the potential TAM reeducation targets for potentiating cancer immunotherapy and the underlying mechanisms are summarized in this review. Moreover, the most recent advances in utilizing nanomedicine for the TAM immunomodulation for augmented cancer immunotherapy are introduced. Finally, we conclude with our perspectives on the future development in this field.